Microreactor generated RAFT imprinted smart hydrogels - Kadhirvel, Porkodi (2014)
Stimuli-Responsive Smart Hydrogels (SRSH) are extensively used in biotechnology and biomedicine amongst many other fields1. SRSH can be obtained conventionally through a batch reactor process resulting in irregular shaped particles, whereas emulsion, inverse-suspension, precipitation polymerizations, etc., lead mostly to spherical shaped particles. Recently micro-reactors have been introduced as an alternative approach to produce spherical/conical particles continuously through implementation of a microfluidic droplet based technique.2 Reversible Addition-Fragmentation Chain Transfer (RAFT) controlled polymerization on the other hand has received a considerable attention in hydrogels provided the potential to produce macromolecules with a narrow molecular weight distribution.3 Having faced some classical deficiencies of conventional Free Radical Polymerization (FRP), owing to the importance of hydrogel particle morphology and the promising behavior of Controlled Radical Polymerization (CRP) using RAFT agent, here we try to combine the continuous flow microreactor and RAFT to overcome the obstacles. Besides, one additional goal is to create molecular memory (imprinting) inside hydrogel network. Pharmaceutical drugs with different classifications are employed as templates to obtain molecular imprinted hydrogels (MIH) in a continuous flow microreactor.